Analisis Kesulitan Keuangan Perusahaan Perbankan dan Lembaga Pembiayaan - Putong, Iskandar; Gani, Engelwati (Binus Business Review, 2012)
Analysis of financial distress at the main company that has sold its shares in an open society (go public) becomes so important because most companies always display the good side of the company in the form of financial reporting data each year. For ordinary people the financial statements audited by a valid and authorized institutions listed on stock exchange by naked eye showed a good performance in finance, but in a more in-depth analysis of the data the form of numbers that will give I different conclusion to the eyes economists and financial analysts to the case. In this study, it is used general sample 4 companies engaged in finance. The Discriminant analysis model using the Altman Z-Score that dissect the financial statements of the company for 3 years showed that not always the companies that have go public must be good financial performance as well. Two of four companies surveyed, in fact, are predicted theoretically bankrupt because the companies were experiencing financial distress.